2020
DOI: 10.1016/j.impact.2019.100198
|View full text |Cite
|
Sign up to set email alerts
|

Engineered metal oxide nanomaterials inhibit corneal epithelial wound healing in vitro and in vivo

Abstract: Ocular exposure to metal oxide engineered nanomaterials (ENMs) is common as exemplified by zinc oxide (ZnO), a major constituent of sunscreens and cosmetics. The ocular surface that includes the transparent cornea and its protective tear film are common sites of exposure for metal ENMs. Despite the frequency of exposure of the ocular surface, there is a knowledge gap regarding the effects of metal oxide ENMs on the cornea in health and disease. Therefore, we studied the effects of metal oxide ENMs on the corne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 72 publications
3
17
0
Order By: Relevance
“…We determined that V 2 O 5 nanoflakes were moderately toxic to RCFs, consistent with our previous study of corneal epithelial cells in vitro 13 as well as other studies on mammalian cells with V 2 O 3 nanotubes, V 2 O 5 NPs, and V 2 O 5 nanotubes. 51 53 In aggregate, these data suggest that nanosized vanadium oxide materials are noxious to cells regardless of their shape or oxidation state.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…We determined that V 2 O 5 nanoflakes were moderately toxic to RCFs, consistent with our previous study of corneal epithelial cells in vitro 13 as well as other studies on mammalian cells with V 2 O 3 nanotubes, V 2 O 5 NPs, and V 2 O 5 nanotubes. 51 53 In aggregate, these data suggest that nanosized vanadium oxide materials are noxious to cells regardless of their shape or oxidation state.…”
Section: Discussionsupporting
confidence: 90%
“… 5 , 21 Thus, it was unsurprising that CuO and ZnO NPs exhibited marked cytotoxicity to corneal fibroblasts consistent with previous studies in other ocular cells types including human corneal limbal epithelial cells and fibroblasts, 14 lens epithelial cells, 41 retinal ganglion cells, 42 and retinal photoreceptors. 43 Although CuO and ZnO NPs decreased cell viability and delayed epithelial and fibroblast migration in the present as well as previous studies, 13 , 14 they did not appear to alter KFM transformation in vitro at the concentrations tested. However, ZnO NPs delayed corneal epithelial migration in vivo and prior studies reported that they induced pulmonary fibrosis and increased myofibroblast expression in vivo, 13 , 44 50 suggesting that further in vitro and in vivo studies are warranted.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…[48] Furthermore, V also exhibits hepatotoxic and nephrotoxic properties containing glomerulonephritis and pyelonephritis. [48][49][50][51][52] Besides, V compounds have an adverse influence on cell viability, [34,35,53,54] may lead to partial degeneration of the seminiferous epithelium of the seminiferous tubules in the testes, and can affect male fertility. [55][56][57][58][59][60][61][62][63][64] So, the biocompatibility of alloying elements in Ti alloys as implant materials becomes an important research area.…”
Section: Ceramicsmentioning
confidence: 99%